Factors influencing creative labor of intellectuals in Vietnamese universities: Empirical insights - Hang, Vu Thi; Toan, Nguyen Quoc; Thuy, Nguyen Thi; Bac, Ha Thi; Huong, Pham Thi Thu; Sang, Do Van (Edelweiss Applied Science and Technology, 2024)
Intellectuals play a critical role in Vietnam's industrialization, modernization, and knowledge-based economy. This study explores the motivating environment fostering creative labor among intellectuals in universities, a key segment of this workforce. Using data from 256 staff members across 30 universities, the research employs expert methods and the Relative Importance Index (RII) to evaluate 16 influential factors. Results show that factors such as salary policies, work supervision, recognition of creative ideas, and intellectuals’ self-learning spirit have the highest impact on fostering creativity. This study highlights the need for comprehensive institutional reforms to enhance intellectual motivation and creativity in higher education, offering actionable insights for policy and practice.